Research Progress in Pediatric Lung Transplantation: A Bibliometric Analysis - Yuan, Quan; Shen, Zixiong; Li, Zhiqin (The Thoracic and Cardiovascular Surgeon, 2025)
Pediatric lung transplantation is considered to be an effective treatment for end-stage lung disease in children, and this study mainly conducts a bibliometric analysis in the field of pediatric lung transplantation.We used the web of science databases to perform a bibliometric analysis of the progress of research in the field of pediatric lung transplantation from 1996 to 2024. In addition, we used VOSviewer software and the “bibliometrix” package in R to visualize and analyze the authors, countries, journals, institutions, and keywords of the literature.We identified 359 literature studies related to pediatric lung transplantation, which were cited 6,387 times by 1,400 journals. The journal with the highest number of average citations was the “New England Journal of Medicine,” while the journals with the highest number of publications were the “Journal of Heart and Lung Transplantation and Pediatric Transplantation.” The United States was the country with the highest number of publications (64.3%), followed by the United Kingdom (11.1%) and Canada (8.08%).Research in the field of pediatric lung transplantation is currently on the rise, while research is still dominated by developed countries, with most developing countries in their infancy. Against the background of COVID-19 and global health challenges, the unique need for pediatric lung transplantation is becoming a trend.
Keywords: pediatric; transplantation; lung; quality of life